Effect of Shenmai injection on the preservation quality of suspended red blood cells prepared from high hemoglobin population in Xizang plateau - ZHONG Rui; HE Zeng; WANG Hong; LI Wanjing; LIU Jiaxin; CAO Ye (Zhongguo shuxue zazhi)
[Objective] To investigate the effect of Shenmai injection on the preservation quality of suspended red blood cells of high hemoglobin population in Xizang plateau. [Methods] Whole blood (400 mL, n=8) collected by the Xizang Autonomous Region Blood Center was centrifuged at 3 000 g for 10 minutes to remove most of the plasma, followed by the addition of 100 mL of MAP preservation solution to obtain plateau suspended red blood cells, which were then divided into three equal portions. One portion was the control group, and another part had 15 mL of MAP preservation solution added, which was the dosage group. The third portion involved diluting Shenmai injection with MAP, followed by addition of 15 mL of MAP preservation solution containing Shenmai to the red blood cells, resulting in a final concentration of Shenmai injection of 1%, which was the Shenmai group. Blood routine, pH value, electrolytes, glucose, lactate, free Hb, adenosine triphosphate (ATP), P50, phosphatidylserine (PS) and other indicators were detected at day 1, 21 and 35, respectively. [Results] The Hb concentration and Hct of the dosage group and the Shenmai group were significantly lower than those of the control group, with values of (179.3±17.8) vs (181.0±17.1) vs (199.1±19.5) g/L for Hb concentration and (53.2±2.6)% vs (53.3±2.5)% vs (58.4±3.1)% for Hct. The three groups maintained this pattern until the end of storage. In the middle and late stages of preservation, the glucose and Na+ contents in the dosage group and the Shenmai group were higher than those in the control group, while the lactate and K+ contents were lower than those in the control group. At the end of storage, the glucose and Na+ content of the Shenmai group was higher than that of the dosage group, while the lactate and K+ content were lower than that of the dosage group. From day 1 to day 35 of storage, the hemolysis rate of the Shenmai group was significantly lower than that of the control group and the dosage group. On day 21 and 35 of storage, the PS expression rate in the Shenmai group was significantly lower than that in the control group and the dosage group, which were (6.52±0.40)% vs (7.24±0.91)% vs (8.27±0.93)% and (7.29±0.53)% vs (9.37±0.82)% vs (8.39±0.76)%, respectively. [Conclusion] The hemolysis rate and PS of suspended red blood cells of Xizang high altitude prepared by adding Shenmai injection were significantly lower than those in the control group and the dosage group, which was conducive to reducing hemolysis and slowing down the aging of red blood cells, and had a certain improvement on the preservation quality of suspended red blood cells in Xizang plateau people.